2014
DOI: 10.1111/aos.12508
|View full text |Cite
|
Sign up to set email alerts
|

1090 nm infrared radiation at close to threshold dose induces cataract with a time delay

Abstract: ABSTRACT.Purpose: To investigate whether infrared radiation (IRR)-induced cataract is instant or is associated with a time delay between the exposure and the onset of lens light scattering after an exposure to just above threshold dose. Methods: Six-weeks-old albino Sprague-Dawley female rats were unilaterally exposed to 197 W/cm 2 IRR at 1090 nm within the dilated pupil. In the first experiment, the animals were exposed with four exposure times of 5, 8, 13 and 20 second, respectively. At 24 hr after exposure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…18,19 The current findings that 96-W∕cm 2 1090-nm IRR with 1-h exposure does not result in direct damage in the lens if the temperature rise is <8°C implicates that IRR-induced cataract is caused by indirect heat absorption in tissues surrounding the lens or, alternatively, possibly by a local inflammatory reaction induced by temperature rise in tissues surrounding the lens, or both.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…18,19 The current findings that 96-W∕cm 2 1090-nm IRR with 1-h exposure does not result in direct damage in the lens if the temperature rise is <8°C implicates that IRR-induced cataract is caused by indirect heat absorption in tissues surrounding the lens or, alternatively, possibly by a local inflammatory reaction induced by temperature rise in tissues surrounding the lens, or both.…”
Section: Discussionmentioning
confidence: 69%
“…Previously, we found that 197 W∕cm 2 1090-nm IRR exposure on the cornea within the dilated pupil for a minimum of 8 s induces cataract with a temperature increase of 10°C in the anterior segment of the eye. 18,19 The purpose of the present study was to investigate if the previously suggested photochemical threshold for near-IRR induced cataract, 1.4 kJ∕cm 2 , 7,14,15 is consistent with irradiance-exposure duration reciprocity, indicating a photochemical nature of cataract formation.…”
mentioning
confidence: 89%
“…The current experiment was designed to elucidate the temperature increase at 8 s exposure to threshold irradiance of 1090-nm IRR for cataract induction 22 with the long-term intention to investigate irradiance exposure time reciprocity below a threshold temperature for cataract induction.…”
Section: Discussionmentioning
confidence: 99%
“…22 The presently used optical setup was designed to result in a close to collimated beam through the optics of the eye by focusing the beam in front of the eye (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation